RELIABILITY OF THE CORTICOTROPIN RELEASING HORMONE STIMULATION TEST FOR DIFFERENTIATING BETWEEN ACTH DEPENDENT AND INDEPENDENT CUSHING SYNDROME - Polat Korkmaz, O. (Acta Endocrinol (Buchar), 2019)
CONTEXT: It is a challenge to determine the origin of Cushing syndrome (CS), especially in patients with low-normal adrenocorticotropic hormone (ACTH) concentrations. OBJECTIVE: To evaluate the reliability of the corticotropin-releasing hormone (CRH) stimulation test in patients with CS whose origin of disease was not clearly identified using ACTH values, the high-dose dexamethasone suppression test (HDDST), and imaging in a single tertiary referral center. DESIGN AND METHODS: Twenty-one patients with CS who were admitted to the endocrinology-metabolism clinic between 2004 and 2016 whose ACTH concentrations were 5-20 pg/mL and needed CRH stimulation test were retrospectively assessed. RESULTS: Nine out of 21 patients were diagnosed as having Cushing’s disease (CD) and 12/21 had adrenal CS. The CRH stimulation test had a sensitivity and specificity of 100% and 8%, and positive and negative predictive values of 100% and 45% according to the current diagnostic criteria, respectively. An increase in ACTH ≥115% at 15 minutes and cortisol ≥86% at 60 minutes after CRH were associated with the highest likelihood ratio. The sensitivity and specificity of ACTH was 67% and 83% (AUC=0.75±0.12, 95% CI: [0.5-0.9]; p=0.03), and for cortisol it was 75% and 78% (AUC=0.71±0.15, 95% CI: [0.5-0.9]; p=0.03). Cortisol suppression of more than 64% from basal level in the HDDST suggested CD with the highest likelihood ratio. When these cut-off values were used together, both tests were negative in the patients with CD. CONCLUSION: The CRH stimulation test has low specificity to localize CS in patients with ACTH concentrations of 5-20 pg/mL according to the current diagnostic criteria. Different diagnostic criteria may be used in the CRH stimulation test and also in the HDDST in this group of patients.